42.1k views
0 votes
Please refer to the picture below.

Please refer to the picture below.-example-1

1 Answer

3 votes

Answer:

Simplify both sides of the equation to get a^2 + 2ab + b^2 - c^2 = 2ab. Then subtract 2ab and add c^2 to both sides of the equation

Explanation:

(a+b)^2 - c^2 = 4(1/2 ab)

Simplify both sides

a^2 + 2ab + b^2 - c^2 = 2ab

Subtract 2ab and add c^2 to both sides

a^2 + 2ab + b^2 - c^2 - 2ab + c^2 = 2ab - 2ab + c^2

a^2 + b^2 = c^2

Answer is the second option

Simplify both sides of the equation to get a^2 + 2ab + b^2 - c^2 = 2ab. Then subtract 2ab and add c^2 to both sides of the equation

User Mrig
by
5.3k points